Application of Off-Grid Solar Panels System for Household Electricity Consumptions in Facing Electric Energy Crisis - Meliala, Selamat; Muhammad Jalil, Saifuddin; Fuadi, Wahyu; Asran, Asran (International Journal of Engineering, Science and Information Technology, 2022)
At this time the cost of electricity is very expensive which is felt by the community because the government is still exploring oil and natural gas which is the need for non-renewable energy sources that are running low. This non-renewable energy still dominates for power generation in the thousands of Mega Watts. To anticipate the problem of non-renewable energy that is so big, you can use the On Grid-Tie System, sunlight is converted into DC voltage through the Solar Module, a pure DC voltage that comes out of the solar module. And Off Grid-Tie System namely sunlight is converted into DC voltage through the Solar Module, pure DC voltage generated from the solar module. Then the pure DC voltage uses a DC to DC regulation module or is called a DC regulator. DC regulator which aims to regulate the storage of DC current into the battery. Then the battery is used to supply power to the inverter. The method used in this study uses an off-grid solar home system as a power supply for households that are far from the electricity network or save electricity consumption due to expensive electricity rates. For settings for the intensity of sunlight using a portable holder, the solar panels are shifted manually in order to get the optimal light intensity to produce large output power. In off-grid application testing at household loads, from a load test of 93.5 watts to 750 watts, it shows that the load current is getting bigger and the discharging current is also large so that the duration of using the off-grid system from a load of 93.5 watts is 6 hours long and at a load of 750 watts. up to 15 minutes. This is because the condition of the lead-acid battery is maintained from 13.56 to 11.5 Volt DC, the battery should not be forced below the 11.5 Volt voltage because it will cause damage to the battery. For the use of loads that respond to very high instantaneous currents such as electric irons, dispensers, rice cookers should use more batteries and use an off-grid system voltage higher than 12 Volt DC.